An Efficient Directly Conversion of the Ethyl p-Methoxycinnamate into N,N-dimethyl-p-Methoxycinnamamide and study the structure-activity relationship on anti-inflammatory activity - Ismiarni Komala (Universitas Gadjah Mada, 2020)
Ethyl p-methoxycinnamate (EPMC) (1) is a major natural ester found in the rhizome of Kaempferia galanga and has been reported to have anti-inflammatory activity. Some of the structural modification of this compound has been carried out in order to study the structure-activity relationship on its anti-inflammatory activity. In the present study, we report a new, simple and efficient procedure in the conversion of the ethyl p-methoxycinnamate into N,N-dimethyl-p-methoxycinnamamide (5) and then study the structure-activity relationship on its anti-inflammatory activity. The reaction was carried out through a microwave-assisted direct amidation between (EPMC) (1) with dimethylformamide (DMF) in the basic condition. The mixture was irradiated by using unmodified microwave-oven at 300 W for 1 minute to obtain compound (5) in 88.8% yields. The extensive analysis of the GCMS and NMR data supported that the product of synthesis is N,N-dimethyl-p-methoxycinnamamide (5). Evaluation of the anti-inflammatory activity of compound 5 by using anti-denaturation of heat bovine serum albumin (BSA) assay indicated that N,N-dimethyl-p-methoxycinnamamide (5) still have anti-denaturation activity. Compound 5 has an amide functional group which is more slowly hydrolyzed if compared to 1. Hence, the reaction has successfully produced a more stable compound which still has anti-inflammatory activity